2013
DOI: 10.1111/jfd.12035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of citrus by‐products fermented with a probiotic microbe on growth performance, innate immunity and disease resistance against Edwardsiella tarda in juvenile olive flounder, Paralichthys olivaceus (Temminck & Schlegel)

Abstract: Two consecutive studies were conducted to evaluate the dietary supplementation of citrus by-products (CB) fermented with probiotic bacteria on growth performance, feed utilization, innate immune responses and disease resistance of juvenile olive flounder. In Experiment I, five diets were formulated to contain 0% (control) or 3% four different CB fermented with Bacillus subtilis (BS), Enterococcus faecium (EF), Lactobacillus rhamnosus (LR) and L. plantarum (LP) (designated as CON, CBF-BS, CBF-EF, CBF-LR and CBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…The chemical composition of the soft body of abalone was not affected by the experimental diets in this study. Previously, Lee et al () also showed that the chemical composition of olive flounder was not affected by the dietary supplementation of citrus by‐products fermented with four different bacteria ( Bacillus subtilis , Enterococcus faecium , Lactobacillus rhamnosus and L . plantarumno ) in the 10‐week feeding trial.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The chemical composition of the soft body of abalone was not affected by the experimental diets in this study. Previously, Lee et al () also showed that the chemical composition of olive flounder was not affected by the dietary supplementation of citrus by‐products fermented with four different bacteria ( Bacillus subtilis , Enterococcus faecium , Lactobacillus rhamnosus and L . plantarumno ) in the 10‐week feeding trial.…”
Section: Discussionmentioning
confidence: 96%
“…peels are rich in numerous biologically active compounds, such as vitamin C, phenolic acids, pectin and flavonoids (Bocco, Cuvelier, Richard, & Berset, ; Manthey & Grohmann, ; Rafiq et al, ) having potential anti‐allergenic, anti‐atherogenic, anti‐inflammatory, antimicrobial, antioxidant, antithrombotic, cardioprotective and vasodilatory effects (Benavente‐García, Castillo, Marin, Ortuño, & Del Rio, ; Middleton, Kandaswami, & Theoharides, ). Several studies on dietary inclusion effects of citrus meal and citrus by‐products fermented on olive flounder ( Paralichthys olivaceus , Temminck & Schlegel) (Lee et al, ; Seo, Kim, Son, & Lee, ) and red sea bream ( Pagrus major Temminck & Schlegel) (Song, Park, Lee, & Lee, ), citrus ( Citrus unshiu Marcovitch) pomace on abalone ( Haliotis discus discus , Reeve) (Jwa & Yeo, ), C. aurantium Linnaeus oil on silver catfish ( Rhamdia quelen Quoy and Gaimard) (Lopes et al, ) and essential oils extracted from bitter lemon ( C. limon Osbeck) peels on fish ( Labeo victorianus Boulenger) (Ngugi, Oyoo‐Okoth, & Muchiri, ) have been reported. Therefore, CPB seems to have high potential as an alternative source for MA in abalone feed as well.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need to control the disease outbreaks in this sector. A concept of a functional feed is an emerging paradigm in aquaculture industry to develop nutritionally balanced diets with functions to control the diseases and culture water system by feed additives (Li and Gatlin 2004;Lee et al, 2013;Wongsasak et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Their results demonstrated that probiotic treatment led to increased myeloperoxidase and lysozyme activities in a dose-dependent manner. 16 Another study on fish using rainbow trout, Oncorhynchus mykiss, as a model revealed that E. faecium enhanced leukocytes superoxide anion production and serum complement activities through the alternative pathway. 17 The study also showed that expression levels of interleukin 1 alpha (IL-1α), Tumor necrosis factor-alpha (TNF-α) and transforming growth factor beta (TGF-β) were increased significantly in the spleen and the kidney.…”
Section: Enterococcus Faecium and Its Effects On The Immune Responsesmentioning
confidence: 99%